Improving population health by reducing poverty: New York's Earned Income Tax Credit - Jeannette Wicks-Lim; Peter S. Arno (Elsevier, 2017)
Despite the established relationship between adverse health outcomes and low socioeconomic status, researchers rarely test the link between health improvements and poverty-alleviating economic policies. New research, however, links individual-level health improvements to the Earned Income Tax Credit (EITC), a broad-based income support policy. We build on these findings by examining whether the EITC has ecological, neighborhood-level health effects. We use a difference-in-difference analysis to measure child health outcomes in 90 low- and middle- income neighborhoods before and after the expansion of New York State and New York City's EITC policy between 1997-2010. Our study takes advantage of the relatively exogenous source of income variation supplied by the EITC-legislative changes to EITC policy parameters. This feature minimizes the endogeneity problem in studying the relationship between income and health. Our estimates link a 15-percentage-point increase in EITC benefit rates to a 0.45 percentage-point reduction in the low birthweight rate. We do not observe any measurable link between EITC benefits and prenatal health or asthma-related pediatric hospitalization. The magnitude of the EITC's impact on low birthweight rates suggests ecological effects, and an additional channel through which anti-poverty measures can serve as public health interventions.